Synthesis of biphasic nanomaterials based on ZnO and SnO2: application towards photocatalytic degradation of acid red dye - Kudale, Ananada S.; Kamble, Santosh B.; Gore, Anil H.; Pisal, Mahesh M.; Salokhe, Anil T.; Kolekar, Govind B.; Helavi, Vasant B. (Nano-Structures & Nano-Objects, 2019)
Zn2SnO4/SnO2 and ZnO/SnO2 biphasic nanocatalysts have been synthesized by a facile solvothermal method using ethylene glycol (EG) as solvent in three different ways maintaining the pH of the solution at either 3 or 9 followed by calcination at 700 °C. The nanocatalysts are characterized by different techniques to investigate their structure, composition, morphology and optical properties. The XRD results indicate the formation of pristine biphasic composites. The UV-absorbance and photoluminescence spectra confirms the formation of biphasic composites as well as presence of large number of defects in the prepared nanocatalysts. The biphasic nanocomposites possess better photocatalytic activity towards the degradation of Acid Red-183 (AR-183) dye than pristine SnO2 and ZnO nanoparticles. This is mainly due to better charge separation, minimal recombination rate of charge carriers and defect-riched structures of nanocatalysts.

Solvent free, environment benign synthesis of 1,4-dihydropyridines and polyhydroquinolines by using heterogeneous Zn/MCM-41 catalyst - Dhengale, Shankar D.; Naik, Vaibhav M.; Kolekar, Govind B.; Rode, Chandrashekhar V.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2021)
Heterogeneous catalysis has been utilized in number of efficient reactions with higher selectivity of the product, more stable, reusable and easy for separation as compared to homogeneous catalysts. Generally, heterogeneous catalysts are prepared by using mesoporous materials, microporous materials, metal oxides and metal organic framework. The mesoporous materials have small particle size and high surface area as compared to the microporous materials. The adsorbent mesoporous materials have highly efficient for the therapeutic applications in chemistry hence it has best as compared to other heterogeneous materials. Herein, we have reported synthesis of 1,4-dihydropyridines and polyhydroquinolines at solvent free and environmental benign condition in the presence of Zn/MCM-41 catalyst. The present protocol gives excellent yield (89-96%) of the product within short reaction time by easy work up procedure and no need of further purification of product. The catalyst was characterized by XRD diffractometer, SEM, EDAX, TGA-DTA, BET surface area analysis and FT-IR Spectroscopy. The synthesized organic compounds were characterized by FT-IR, H-1 NMR, C-13 NMR, LC-MS spectrometry.
Keywords: High activity; High selectivity; mesoporous materials; microporous materials; Reusability of catalyst

Synthesis of indeno-[1,2-b]-quinoline-9,11(6H,10H)-dione and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-dione derivatives in presence of heterogeneous Cu/zeolite-Y as a catalyst - Dhengale, Shankar D.; Rode, V. Chandrashekhar; Kolekar, Govind B.; Anbhule, V. Prashant (RSC Advances, 2022)
A simple method for the synthesis of indeno-[1,2-b]-quinoline-9,11-(6H,10H)-dione derivatives and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-diones through the reaction of aromatic aldehydes, indan-1,3-dione, dimedone, and p-toluidine/ammonium acetate in the presence of heterogeneous CuO supported on a zeolite-Y catalyst has been investigated in ethanol under reflux conditions. By this method, the reaction time has been reduced, giving an excellent yield of the product. The catalyst was prepared by a hydrothermal method followed by a wet impregnation method. The catalyst had shown Bronsted acid sites and Lewis acid sites. The used catalyst could be actively recycled with a marginal decrease in yield up to five recycles. The prepared catalyst was characterized by FT-IR, pyridine FT-IR, XRD, SEM, EDS, XPS, TEM, and BET surface area analysis. The synthesized compounds were characterized by FT-IR, H-1 NMR, C-13 NMR and GC-MS spectroscopy.

Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction